2013
DOI: 10.1093/carcin/bgt143
|View full text |Cite
|
Sign up to set email alerts
|

RIP1 potentiates BPDE-induced transformation in human bronchial epithelial cells through catalase-mediated suppression of excessive reactive oxygen species

Abstract: Cell survival signaling is important for the malignant phenotypes of cancer cells. Although the role of receptor-interacting protein 1 (RIP1) in cell survival signaling is well documented, whether RIP1 is directly involved in cancer development has never been studied. In this report, we found that RIP1 expression is substantially increased in human non-small cell lung cancer and mouse lung tumor tissues. RIP1 expression was remarkably increased in cigarette smoke-exposed mouse lung. In human bronchial epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 49 publications
0
62
0
Order By: Relevance
“…We found that the synthesis rate of catalase was suppressed substantially, whereas the stability of this ROS scavenging protein was decreased slightly within RIP1 knockdown cells, suggesting a dual regulation for catalase expression. This is distinct from the carcinogen benzo(a)pyrene diolepoxide-induced catalase suppression that mainly occurs through proteasomal degradation in immortalized human bronchial epithelial cells (33). These observations suggest that the regulation of catalase expression is complex and, again, may be cell type-or stimulation-specific.…”
Section: Discussionmentioning
confidence: 80%
“…We found that the synthesis rate of catalase was suppressed substantially, whereas the stability of this ROS scavenging protein was decreased slightly within RIP1 knockdown cells, suggesting a dual regulation for catalase expression. This is distinct from the carcinogen benzo(a)pyrene diolepoxide-induced catalase suppression that mainly occurs through proteasomal degradation in immortalized human bronchial epithelial cells (33). These observations suggest that the regulation of catalase expression is complex and, again, may be cell type-or stimulation-specific.…”
Section: Discussionmentioning
confidence: 80%
“…Catalase expression is regulated through different mechanisms including proteasomal protein degradation and miRNA-mediated protein synthesis suppression (25,(36)(37)(38). We found that miR-551b, which is predicted to target the 3′UTR of catalase mRNA, was increased in AR cells and knockdown of miR-551b strongly rescued catalase expression, suggesting an important mechanism in the upregulation of MUC1 through miR-551b-mediated catalase suppression.…”
Section: Discussionmentioning
confidence: 93%
“…We found MUC1 mRNA was increased in AR cells, which was associated with ROS accumulation resulting from catalase inhibition. ROS activated MAPKs, including ERK, which stimulates MUC1 transcription (38,45). Thus, it is possible that activation of transcription is involved in increased MUC1 expression in AR cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study data of Leuk cells also confirmed that CSE augmented RIP2 expression. A recent study suggested that RIP1 expression remarkably increased in cigarette smokeexposed mouse lung and was significantly induced by CSE in human bronchial epithelial cells [36]. As members of receptor-interacting protein family, RIP1 and RIP2 share many common functions in cell death and cell stress signaling [37].…”
Section: Discussionmentioning
confidence: 99%